Prolonged treadmill training is not able to prevent ovariectomy-induced bone loss - Massing, Tim; Will, Konstantin; Müller, Michael; Aleith, Johann; Lindner, Tobias; Warkentin, Mareike; Müller-Hilke, Brigitte; Mittlmeier, Thomas (Frontiers in Physiology, 2022)
Introduction: Exercise is widely recognized as prophylaxis for osteoporosis. However, exactly which type of exercise is best to prevent loss of bone mass remains undefined. To find an appropriate form of treadmill exercise that would ameliorate postmenopausal loss of cortical and trabecular structures, we compared various training regimen in ovariectomized (OVX) C57BL/6J mice. Methods: Common to all regimen were training durations of 14 weeks including five 30 min-sessions per week. Two groups—one sham operated, one OVX—served as controls that did not perform any training. Three OVX groups ran at constant speed, either without any incline or at 20° in- and 20° decline, respectively. An additional OVX group ran an interval training, an alternation between intensive tempo sections and so-called slower regeneration phases. Femoral and humeral bone structures were assessed via micro-computed tomography (μCT), biomechanical stability of the femora via 3-point bending test, muscle volumes of the posterior extremities via magnetic resonance imaging (MRI), and bone metabolic parameters via ELISA on peripheral blood. Result: OVX resulted in loss of bone mass and stability and a transient rise in the N-terminal collagen type I pro-peptide (PINP). Training resulted in increased muscle volumes of the heart and the lower extremities as well as increased running velocities. However, none of the exercise programs was able to prevent ovariectomyinduced loss of bone mass. Discussion: These data therefore suggest that axial loading and tensile strain do not suffice as prophylaxis for postmenopausal osteoporosis yet may need to be complemented by low dose pharmaceutics or dietary supplements.